Muslim Perceptions of Sharia Contracts in Home Financing at Bank Syariah Indonesia - Danial Paripurna; Muhajirin Muhajirin; Nur Hidayah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the level of Muslim consumer awareness of Sharia contracts in financial transactions, their perceptions of Islamic Home Ownership Credit (KPR) products, and the strategies implemented by Bank Syariah Indonesia (BSI) in addressing the challenges of Sharia-compliant mortgage implementation. Using a qualitative approach with a literature study method, data were collected from various academic sources, official reports, and publications from financial institutions and government agencies. The findings indicate that the level of Sharia financial literacy among the public remains low, resulting in limited understanding of contract principles such as murabahah, istisna’, ijarah muntahiya bit tamlik, and musharakah mutanaqisah. Consumer perceptions also reveal doubts regarding the implementation of contracts, which are often viewed as deviating from Sharia principles. Meanwhile, BSI's strategies focus on institutional consolidation, expanding financial literacy, and offering competitive products to build trust and enhance Sharia financial inclusion. This study recommends increasing public education and ensuring transparency in contracts to strengthen public trust in Sharia-compliant mortgage products.